Hak-hak Kewarganegaraan dalam Kerangka Negara Hukum : Kajian Teoretis dan Praktis di Indonesia - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Nabhan Tabarok; Muti'ah Nuha Mumtazah; Hannamuddin Wafiyur Rahman (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
This study discusses citizenship rights within the framework of the rule of law in Indonesia, focusing on both theoretical and practical aspects. Citizenship is a crucial element in the legal system, as it grants individuals legal status, through which they can access civil, political, and social rights. However, despite the constitutional guarantee of citizenship rights, their implementation in Indonesia still faces various challenges, particularly regarding stateless individuals, children from mixed marriages, and limited access to citizenship documents. This research employs a normative juridical and comparative method by analyzing Indonesia's citizenship regulations and comparing them with countries such as Canada and Germany. The findings indicate that Indonesia needs to reform its citizenship policies to be more inclusive and aligned with international standards. Recommendations include addressing statelessness issues, simplifying the administrative process for obtaining citizenship, and aligning policies with international principles. Therefore, it is expected that Indonesia's citizenship policies can provide more equitable and fair protection for all its citizens.